2018
DOI: 10.1007/s11060-018-2791-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of dasatinib, lenalidomide, and temozolomide in children with relapsed or refractory central nervous system tumors

Abstract: Single agent studies targeting the tumor microenvironment in central nervous system (CNS) tumors have largely been disappointing. Combination therapies targeting various pathways and cell types may be a more effective strategy. In this phase I study, we evaluated the combination of dasatinib, lenalidomide, and temozolomide in children with relapsed or refractory primary CNS tumors. Patients 1-21 years old with relapsed or refractory CNS tumors were eligible. Starting doses of dasatinib and lenalidomide were 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Additionally, lenalidomide can induce tumor cell apoptosis and act as an immune-modulator by stimulating T-cell proliferation, reducing the expression of immune-checkpoint inhibitors on both T and NK cells, inhibiting TNF-alpha and reducing T-regulatory cells. Some interesting reports have shown its efficacy in treating CNS relapse and its ability to cross the blood-brain barrier (BBB) [ 15 , 16 , 17 ]. Temozolomide, on the other hand, is an alkylating chemotherapy agent that is used in a variety of solid and CNS tumors, and which has excellent BBB penetration [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, lenalidomide can induce tumor cell apoptosis and act as an immune-modulator by stimulating T-cell proliferation, reducing the expression of immune-checkpoint inhibitors on both T and NK cells, inhibiting TNF-alpha and reducing T-regulatory cells. Some interesting reports have shown its efficacy in treating CNS relapse and its ability to cross the blood-brain barrier (BBB) [ 15 , 16 , 17 ]. Temozolomide, on the other hand, is an alkylating chemotherapy agent that is used in a variety of solid and CNS tumors, and which has excellent BBB penetration [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Identifying patients who could potentially benefit from combining POM with other anticancer agents may enhance the level of activity observed in clinical trials. A phase 1 trial examined the combination of dasatinib, lenalidomide, and temozolomide in pediatric patients with either relapsed or refractory CNS tumors ( 27 ). The trial established feasibility of the combination; however, any efficacy data were preliminary, and it remains to be determined whether an efficacy benefit exists.…”
Section: Discussionmentioning
confidence: 99%
“…For Src inhibitors, KX2–391 has only proven to be a favorable pharmacokinetic profile and be well tolerated in patients with advanced malignancies in phase I trial [32] but not been reported in any brain tumors. Dasatinib has been reported to undertake phase I trial in children with relapsed or refractory central nervous system tumors and preliminary evidence of clinical benefit was seen [60].…”
Section: Discussionmentioning
confidence: 99%